The Problem of Preservation and Development of Ukrainian Language in Foreign Language Environment - Svitlana Romaniuk (Pedagogical Discourse, 2016)
The article explores the place of Ukrainian language in the vital activity of Ukrainians abroad, its importance as a means of communication and existence of the ethnic group is proved. It is mentioned that the language is one of the main, but not the only basic element of identification of a Ukrainian, because knowledge of the language depends on many factors, and in the first place out-of-language factors, among which a crucial role is played by the official (or unofficial) governments policy, aimed at supporting or at denationalization of ethnic minorities, the activities of the ethnic community itself concerning the preservation and development of the native language, their living conditions in the countries of settlement.The results of the monitoring as for the number of people, who study Ukrainian language, and the educational institutions, which are shown a preference in teaching the language are presented, the peculiarities of functioning of Ukrainian language in the leading English-speaking countries of the world (Australia, Great Britain, Canada, the USA) are revealed, and the needs of Ukrainians abroad in mastering Ukrainian language are cleared out. It is proved that bilingual training programs, that give some benefits for entering higher educational institutions of the countries of residence and Ukraine, stimulate the learning of Ukrainian language by Ukrainians living abroad. The problems of spreading and adoption of Ukrainian language in the English-speaking environment are shown. It is indicated that the determining factor in this multidimensional process is not the textbooks, but the language environment, which influences the level of mastering of the native (second/foreign) language by the descendants of immigrants. The expediency of use in teaching Ukrainian as a second language methods, techniques and means, which have been proliferated and proved the efficiency in the state schools, of new teaching approaches (communication, functionality), that provide intensive mastering of Ukrainian language and its active application in the real conditions of vital activity of Ukrainians in the multi-lingual environment of the countries of dwelling, are grounded. It is argued that the proper level of functioning of Ukrainian language outside of the Ukrainian state today can only be ensured taking into account the specifics of the environment, with a sincere interest in Ukrainian language among children and parents, and in the same time with a well-designed school system, properly selected curricula, modern methods, well-compiled books, adapted to today’s needs, modern didactic manuals, qualified personnel and, undoubtedly, support by independent Ukraine.Key words: Ukrainian language, assimilating, integration processes, diaspora, lingual-didactic problems, ethnic minorities.